Home Oxygen Program review: Regionalization in Vancouver Coastal Health and British Columbia - Sandberg, Dan (Can J Respir Ther, 2015)
Since its inception in the 1980s, the Home Oxygen Program in British Columbia was centrally managed by the Ministry of Health. Initially a small program with few clients across the province, it soon became a large program with many clients and increasing expenditures. A pilot program started in Victoria (British Columbia) in 1996 demonstrated that managing the program locally could offer better client care, better contract management and significant cost savings. In 2002, the pilot’s model and recommendations were implemented in British Columbia’s five health authorities. The present review details the experiences of regionalizing the program in the Vancouver Coastal Health authority. After fine adjustments to the model were developed and new contracts and criteria changes made, better care for clients was provided than the previous centralized model at a reduced cost to the taxpayer.